2020
DOI: 10.1101/2020.07.30.228460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenomic analysis of SARS-CoV-2 genomes from western India reveals unique linked mutations

Abstract: India has become the third worst-hit nation by the COVID-19 pandemic caused by the SARS-CoV-2 virus. Here, we investigated the molecular, phylogenomic, and evolutionary dynamics of SARS-CoV-2 in western India, the most affected region of the country. A total of 90 genomes were sequenced. Four nucleotide variants, namely C241T, C3037T, C14408T (Pro4715Leu), and A23403G (Asp614Gly), located at 5'UTR, Orf1a, Orf1b, and Spike protein regions of the genome, respectively, were predominant and ubiquitous (90%). Phylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
4
19
1
Order By: Relevance
“…Apart from these four mutations, the nsp3 protein region within ORF1a also displayed a higher frequency of mutations, G4354A, A4372G, C5700A, C6027T, C6573T, the latter three being missense mutations. Of these, C5700 along with a silent C313T mutation has been reported to co-occur in samples collected from Western state of Maharashtra, India 16 . The nsp4 and nsp5 proteins each harbored one high frequency missense mutation each namely C9693T and C10815T, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from these four mutations, the nsp3 protein region within ORF1a also displayed a higher frequency of mutations, G4354A, A4372G, C5700A, C6027T, C6573T, the latter three being missense mutations. Of these, C5700 along with a silent C313T mutation has been reported to co-occur in samples collected from Western state of Maharashtra, India 16 . The nsp4 and nsp5 proteins each harbored one high frequency missense mutation each namely C9693T and C10815T, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Such a reduction in viral titers on BCG administration have also been seen in case of other viruses like respiratory syncytial virus, influenza A virus and herpes simplex virus type 2 possibly through macrophage activation [29-31]. However this sensitivity was not seen in later half of the study indicating that perhaps there were 2 strains of the virus as suggested by Paul et al [32]. Sequencing the virus strains is underway at present which will make this clear and could possibly provide an explanation of the heterogeneous nature of Covid-19 progression and outcomes in various populations and/or in the same population /center at different times.…”
Section: Discussionmentioning
confidence: 59%
“…G4354A, A4372G, C5700A, C6027T, C6573T, the latter three being missense mutations. Of these, C5700 along with a silent C313T mutation has been reported to co-occur in samples collected from the Western state of Maharashtra, India [31]. The nsp4 and nsp5 proteins each harboured one high-frequency missense mutation each namely C9693T and C10815T, respectively.…”
Section: Resultsmentioning
confidence: 99%